FDI in Indian retail – and its implications - Natarajan Chandrasekhar (Global Economic Observer)
The health of a nation is gauged not only by the quantum of FDI it attracts but also the trend it follows. In turn this is dependent on the economic policies formulated and practiced and the willingness of all concerned to engage with global economic practices. Since the early 1990’s when the government embarked on a policy of liberalization it has been observed that FDI inflows showed a steady increase until the last couple of years when in fact there has been a de-growth particularly 2010 over 2009 by almost 30%. On the other hand China has attracted FDI more than 4 times the quantum of India during the same period. Investors will look to invest in ‘opportunities’ as they see bearing the most attractive returns within a given frame work considering both the ‘home’ as well as ‘host’ country. Facts and figures very clearly indicate the positive impact even in India for certain sectors when FDI has been embraced. On the other hand, India most urgently requires gathering as much as investment as is possible to keep the momentum of growth going and one such opportunity is the organizing of our retail segment which would support development endeavor in a big way. The issue of embracing partial FDI in retail has seen some level of procrastination which requires more urgent and serious attention. Can India afford to lose this opportunity? This paper attempts to study the implications for this investment as also providing some suggestions.